1996
DOI: 10.1002/(sici)1097-4679(199609)52:5<525::aid-jclp5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Faking the MMPI-2: Utility of the Subtle-Obvious scales

Abstract: We explored the effect of different subject response sets on the profile configuration of the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) and the utility of traditional validity, Back F, and Subtle-Obvious scales in detecting response set. College students were administered the MMPI-2 under one of three response sets; faking good, faking bad, or standard report. Results revealed significant differences across the three response set groups on all clinical, content, validity, obvious, and two of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…When the MMPI was taken under faking instructions, the MMPI fake-good indices (Baer, Wetter, & Berry, 1992), only one article using O Ϫ S was included and therefore could not be evaluated effectively (although the effect size was large). However, there are several studies (e.g., Bagby, Buis, & Nicholson, 1995;Bagby, Rogers, & Buis, 1994;Brems & Harris, 1996;Grow, McVaugh, & Eno, 1980;Woychyshyn, McElheran, & Romney, 1992) that support the O Ϫ S index as one of the best indices for detecting fake-good MMPI/MMPI-2s, and some (e.g., Brems & Harris, 1996) support that it may add additional information to the traditional validity scales. An indirect implication of the present study is that, given that not all the subtle subscales showed the paradoxical effect, the O Ϫ S index might be modified to include the subscales with the best differentiating results (e.g., perhaps on D and Hy).…”
Section: Discussionmentioning
confidence: 99%
“…When the MMPI was taken under faking instructions, the MMPI fake-good indices (Baer, Wetter, & Berry, 1992), only one article using O Ϫ S was included and therefore could not be evaluated effectively (although the effect size was large). However, there are several studies (e.g., Bagby, Buis, & Nicholson, 1995;Bagby, Rogers, & Buis, 1994;Brems & Harris, 1996;Grow, McVaugh, & Eno, 1980;Woychyshyn, McElheran, & Romney, 1992) that support the O Ϫ S index as one of the best indices for detecting fake-good MMPI/MMPI-2s, and some (e.g., Brems & Harris, 1996) support that it may add additional information to the traditional validity scales. An indirect implication of the present study is that, given that not all the subtle subscales showed the paradoxical effect, the O Ϫ S index might be modified to include the subscales with the best differentiating results (e.g., perhaps on D and Hy).…”
Section: Discussionmentioning
confidence: 99%
“…In order to combat social desirability, subjects are encouraged to be honest, lie scales are added, and items with known and/or comparable social desirability values are selected (Brems & Harris, 1996). These measures assume that subjects are potential cheaters.…”
Section: Introductionmentioning
confidence: 99%
“…B. Schlafstörun-gen). Werden offensichtliche Items überzufällig häufiger bejaht als subtile, kann das gegen die reale Erlebnisqualität der beklagten Symptome sprechen[5].Dabei wird ein Demenztest hier im Sinne eines Symptomvalidierungstests (also als Vergleichspool von Items mit geringer Lösungsschwierigkeit) zur Motivationsdiagnostik und nicht zur differenziellen Beurteilung des realen kognitiven Leistungsniveaus verwendet. Abgleich der Beschwerden und Leistungstestergebnisse mit dem Untersuch ungsverhalten.…”
unclassified